História da formação de professores no Brasil: análise crítica das políticas de formação, por vídeos da década de 1990 - Luiz Junior, Celso (2013)
During the mid 1970s, the system was invented VHS. Since then, the production and dissemination of popular videos and attained the dimension of teacher training. In this context, also emerged the concept of school productive and accessible to the whole population, leading the state to offer continued education policies for teachers of basic education, in order to alleviate problems of initial preparation of these teachers, preparing them for democratic society that loomed on the horizon. This analysis is a method contextualization of these programs, with a view to experiences that occurred in the state of Paraná, through critical reflection of the history of education and educational policies aimed at teaching task in Brazil. Founded in critical theories of curriculum, aims to shed light on processes called: continuing education, continuing education, in-service training offered to teachers of basic education through continuing education programs for videos of the 1990s. So, were used as sources the official texts, such as educational law, literature on the subject, testimony of teachers and graduates of these courses of the videos presented in these courses as an indication of our employees. Therefore, it was the following path: in the first part of the text, drew up an overview of the history of teacher education in Brazil since the first initiatives with the Jesuits (1530) until the period of the military dictatorship (1985), in second part, there was a discussion about teacher education in contemporary society and in the third part was tracing the methodological approach of qualitative research in education, in the fourth part we sought to deepen the understanding of the distance courses offered in the 1990s by of Teleaulas. It is considered that the training project presented in 1990, consistent with the historical tradition of lighter training of teachers in Brazil, especially for teachers of peripheral cities which, during life, had no access to proper qualification, fitting them training, retraining and in-service training. It is further considered that there is a certain optimism exacerbated by the use of information and communication technologies in teaching office and modernizing discourse that can camouflage conservative policies. Thus, the history of education can be a way of uncovering such processes in order to think about the present